POLITIK ISLAM INDONESIA DAN TANTANGAN GLOBAL - Murniati Murniati (An-Nida : Jurnal Komunikasi Islam, 2015)
In long history of NKRI , Islam politics in Indonesia has the own color. Islam came to Indonesia for about twelve century by peace way. On 1945, all of the Indonesian people struggled to get a freedom. Meanwhile, now the struggle of Islam is to come out the Islamic people from global capitalism. Pancasila, as an Indonesian ideology, is the foundation of stated life that is used as guidance in behaving. Since Indonesia was independent, the Islamic people must own effort to create advancement. On the old and new colonial period, the Islamic people did not get the space of aspiration and politics. However, since the coming of Reformation era, the Islamic people started getting public space. Keywords: politics, Islam, and global challenge. Politik Islam Indonesia dalam perjalanannya menjadi warna tersendiri dalam sejarah panjang Negara Kesatuan Republik Indonesia. Islam masuk ke Indonesia sekitar abad ke-12an Islam dengan jalan damai. Pada tahun 1945 seluruh penduduk Indonesia berjuang untuk merdeka, sedangkan kondisi sekarang ini perjuangan Islam adalah membawa umat Islam keluar dari kapitalisme global. Pancasila sebagai ideologi Indonesia adalah dasar kehidupan bernegara yang digunakan sebagai pedoman dalam berperilaku. Sejak Indonesia merdeka, umat Islam terus berusaha untuk berkembang. Di era orde lama dan orde baru umat Islam belum mendapatkan ruang aspirasi dan berpolitik, namun sejak era reformasi umat Islam mulai mendapatkan ruang publik. Kata kunci: Politik, Islam dan Tantangan Global